2018
DOI: 10.1111/jep.12904
|View full text |Cite
|
Sign up to set email alerts
|

Single‐use flexible bronchoscopes compared with reusable bronchoscopes: Positive organizational impact but a costly solution

Abstract: Organizational impact should be considered when assessing MDs. We show in this study that from an organizational viewpoint, there are many advantages to using single-use bronchoscopes. However, in economic impact, it is more cost-effective for our institution, with more than 1500 bronchoscopies performed annually, to use reusable devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…Disposable scopes are used for biopsies in limited circumstances. Disposable scopes are cost effective in lower volume hospitals where <200 FBs are performed every year (4,5).…”
Section: Diagnostic Bronchoscopymentioning
confidence: 99%
“…Disposable scopes are used for biopsies in limited circumstances. Disposable scopes are cost effective in lower volume hospitals where <200 FBs are performed every year (4,5).…”
Section: Diagnostic Bronchoscopymentioning
confidence: 99%
“…As SUFBs do not require any reprocessing after use, the risk of transmission of infectious particles to HCP is reduced by minimising exposure to fomites or aerosols. The portable screens are also easy to clean and a less complex circuit allows for easier tracing of any potential contaminants [14].…”
Section: Advantages Of Single-use Flexible Bronchoscopes Over Reusablmentioning
confidence: 99%
“…The ability of trainees to learn is limited while current recommendations advise that only essential personnel are allowed into the room during bronchoscopy [2,9,24,25]; however, the video function on SUFBs allows you to easily record and store images which can be used to demonstrate clinical anatomy and pathology [14] from a remote location where social distancing can easily be observed. They are also useful as general teaching aids such as simulation training with mannequins which has been shown to reduce the amount of subsequent damage to RFBs [28,29].…”
Section: Advantages Of Single-use Flexible Bronchoscopes Over Reusablmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research with a single-use bronchoscope, the Ambu aScope 4 Broncho, clearly demonstrated the positive organisational impact created by a single-use device, reducing the number of support processes needed to ensure the provision of a clean and ready-to-use bronchoscope. 13 Furthermore, the single-use bronchoscope has been proven to reduce the delay between the indication for bronchoscopy and the initiation of the actual procedure, while having a comparable environmental impact compared to reusable bronchoscopes. 14,15 Although there is limited published evidence to support the use of single-use rhinolaryngoscopes, it is likely that the benefits of single-use bronchoscopes will also apply to single-use rhinolaryngoscopes as the reprocessing procedure is similar.…”
Section: Introductionmentioning
confidence: 99%